Comparative Study between Continuous Epidural Analgesia and Continuous Femoral Nerve Blockade for Pain Relief Following Total Knee Replacement Surgery - Shilpi Vishnoi; Aditi Bharat Jain; Ashok Hirabhai Patel (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Total knee replacement surgery (TKR) is one of the most painful orthopaedic procedures, mandating effective postoperative pain management. Traditionally postoperative analgesia following TKR is provided by intravenous patient controlled analgesia, epidural analgesia and peripheral nerve blocks. Femoral nerve blockade is good analgesia method. Aim and Objectives: To compare VAS scores at different time intervals, requirement of rescue analgesics and incidence of postoperative side effects or complications related to these techniques in postoperative period. Methodology: A prospective observational study and done in Department of Anaesthesia at Sterling Hospital, Ahmadabad Gujarat over a period of six month (April 2017 to September 2017). Total 60 patients of age 50-75 yrs, ASA grade I and II undergoing for total knee replacement surgery were included in the study. Results: Analysis revealed that there was significant difference observed in VAS scores between both groups. When ANOVA test was applied in two time interval ( first 6 hrs and after 6 hrs ) mean of VAS scores in group F is greater than group E before 6 hrs and in 6 to 48 hrs mean VAS scores of group E is more than group F. In three time interval ( 1 to 6 hrs, 6 to 24 hrs, 24 to 48 hrs) ANOVA test mean VAS score of group F more than group E in 1 to 6 hrs and 6 to 24 hrs while in 24 to 48 hrs mean VAS score of group E more than group F. VAS scores of one time interval are compared with VAS scores of other two time interval in post hoc test. The difference is significant at the .05 level. So VAS scores in one time interval is significantly different from other two time intervals. Need of rescue analgesia were more in patient of group F in 1-6 hrs. Incidence of hypotension, nausea and vomiting were not statistically significant in group E and group F. Conclusion: Analysis revealed that there was significant difference observed in VAS scores between both groups. Epidural analgesia was found to be superior than continuous femoral blockade in pain relief in first 6 hrs. Need of rescue analgesia were more in patient of femoral nerve block in first six hours.